A Multi-Dimensional Approach to Measure the Use of Social Media Tools in Accessing Health Information: A Case Study of Griffith University Students, Queensland, Australia - Gudes, Ori; Usher, W. (Association for Computing Machinery, 2013)
of students using Mobile Wireless Communication Technology(MWCT) and Social Media tools (SM) for accessing health information. It was specifically concerned with whether there was a spatial pattern based on students’ location or other social characteristics. An online survey was designed and utilised to collect quantitative, qualitative and spatial data. This study is unique, as it provides multi-dimensional empirical evidence (i.e., quantitative, qualitative, and spatial evidence) that underlies and complements each other. Our findings indicate that there is some evidence of a pattern as to who uses these tools more extensively for accessing health information. For example, families with kids, people who live with partners etc. Proximity to campus was not found to be correlated, and no spatial structure was found in relation to the question: Who used or did not use MWCT to access health information? Therefore, this paper argues for the inclusion and expansion of health information utilising MWCT and SM tools amongst students, which, in turn, complements traditional methods to accessing health information. The study uses a multi-dimensional approach in obtaining empirical evidence. Utilising quantitative, qualitative, and spatial analysis, our analysis instruments are interweaved and complement each other. This also provides unique robustness to this study because of the variety of evidence provided. Potentially, the findings of this paper can be used by other organisations to promote the development of new approaches and the development of online tools to encourage the access of health information by university students. This, in turn, may play a positive role in their health status.